2015
DOI: 10.1105/tpc.15.00471
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Dynamics Driving MAMP-Triggered Immunity and Pathogen Effector-Mediated Immunosuppression in Arabidopsis Leaves Following Infection with Pseudomonas syringae pv tomato DC3000

Abstract: Transcriptional reprogramming is integral to effective plant defense. Pathogen effectors act transcriptionally and posttranscriptionally to suppress defense responses. A major challenge to understanding disease and defense responses is discriminating between transcriptional reprogramming associated with microbial-associated molecular pattern (MAMP)-triggered immunity (MTI) and that orchestrated by effectors. A high-resolution time course of genome-wide expression changes following challenge with Pseudomonas sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(176 citation statements)
references
References 135 publications
10
160
0
3
Order By: Relevance
“…Transcriptome analyses have revealed that 44% of Arabidopsis genes are differentially regulated after inoculation with P. syringae (63). Similarly, U. maydis induces transcriptional reprogramming of up to 21% of maize genes (28).…”
Section: Reprogramming the Host: Effectors Manipulating Host Gene Expmentioning
confidence: 99%
“…Transcriptome analyses have revealed that 44% of Arabidopsis genes are differentially regulated after inoculation with P. syringae (63). Similarly, U. maydis induces transcriptional reprogramming of up to 21% of maize genes (28).…”
Section: Reprogramming the Host: Effectors Manipulating Host Gene Expmentioning
confidence: 99%
“…To go beyond earlier studies that analyzed the JA transcriptional response with a limited number of time points, we generated a high-resolution time series of JA-mediated transcriptional reprogramming in Arabidopsis leaves. Previously, similar types of dense time series experiments with Arabidopsis have been successfully utilized to help decipher gene regulatory networks underpinning a variety of biological processes, such as senescence and responsiveness to infection by Botrytis cinerea and Pseudomonas syringae (Breeze et al, 2011;Windram et al, 2012;Lewis et al, 2015). Here, we used RNA-seq technology to profile whole-genome transcriptional expression in Arabidopsis leaves just before the treatments (t = 0 h), and over 14 consecutive time points within 16 h following application of methyl JA (MeJA; which is readily converted to JA) or a mock solution to the leaves of intact plants (Supplemental Data Set 1).…”
Section: A Time Course Of Meja-elicited Transcriptional Reprogrammingmentioning
confidence: 99%
“…In contrast to previous studies that used a single genetic isolate of the pathogen and different time points as source of variation, this analysis is based on natural genetic variation in the pathogen, which allows for a new perspective (Windram et al, 2012;Howard et al, 2013;Lewis et al, 2015). We first calculated the nonparametric Spearman's rank correlation coefficient of model-corrected transcript means for all gene The relationship of camalexin and lesion area measured on leaves from three Arabidopsis genotypes at 72 HPI with 96 B. cinerea isolates was compared using model-corrected means.…”
Section: Variation Of Arabidopsis Gene Coexpression Networkmentioning
confidence: 99%